Implementation of Harmonized Food Consumption Data Collection in the Balkan Region According to the EFSA EU Menu Methodology Standards - Gurinović, Mirjana; Nikolić, Marina; Zeković, Milica; Milešević, Jelena; Kadvan, Agnes; Ranić, Marija; Glibetić, Maria (Frontiers in Nutrition, 2022)
Initiatives in the Capacity Development in Nutrition Research in the Balkan region in the last decade have been toward the creation of contemporary, harmonized Research Infrastructure (RI) compliant with European standards. This study describes the process of creation and implementation of the European Food Safety Authority (EFSA) EU Menu methodology in the Balkan region during the EFSA support projects for Food consumption data collection in four countries (Serbia, Montenegro, Bosnia and Herzegovina, and North Macedonia). This process entailed the application and improvement of an innovative tool, the DIET ASSESS & PLAN (DAP), a platform for standardized food consumption data collection and dietary intake assessment. DAP comprises computerized food consumption, anthropometric measurements and physical activity questionnaires, validated food picture book and FoodEx2 exposure hierarchy with sets of facet descriptors of the interest. It hosts Balkan food platform with a Serbian food composition database (FCDB) and Regional FCDB, compliant with European Food Information Resource (EuroFIRTM) standards. The implementation of the DAP platform in national dietary surveys conducted with the support of the EFSA EU Menu project in Balkan countries enabled harmonized food consumption data compilation and reporting. Application of the methodology entailed the development of study protocol and extensive education and training of study personnel. The entire data collection process was managed by internal and external survey coordinators. A pilot study was conducted to test the entire data collection and control process and was afterwards used to make necessary improvements and adjustments to meet EU Menu requirements. Data collected is internationally comparable with food consumption data in other European countries within the framework of EU Menu program. Existence of such data in the Balkan region will catalyze research activities in emerging topics such as: identification of dietary patterns, the establishment of national nutrient reference values and food based dietary guidelines (not only in Serbia, but in the whole Balkan region), dietary exposure assessments, the endorsement and evaluation of new food legislations, the environmental and other effects of diet on the food system. The developed and implemented methodology underpins evidence-based policy-making processes lacking in the field of public health nutrition in the region.